Transitional and Long-Term Care System in Japan and Current Challenges for Stroke Patient Rehabilitation - Kinoshita, Shoji; Abo, Masahiro; Okamoto, Takatsugu; Miyamura, Kohei (Frontiers in Neurology, 2022)
In Japan, the national medical insurance system and long-term care insurance (LTCI) system cover rehabilitation therapy for acute, convalescent, and chronic stroke patients. Medical insurance covers early and multidisciplinary rehabilitation therapy during acute phase hospitalizations. Patients requiring assistance in their activities of daily living (ADL) after hospitalization are transferred to kaifukuki (convalescent) rehabilitation wards (KRW), which the medical insurance system has also covered. In these wards, patients can receive intensive and multidisciplinary rehabilitation therapy to improve their ADL and transition to a smooth home discharge. After discharge from these hospitals, elderly stroke patients can receive outpatient (day-care) rehabilitation and home-based rehabilitation using the LTCI system. The Japanese government has proposed building a community-based integrated care system by 2025 to provide comprehensive medical services, long-term care, preventive care, housing, and livelihood support to patients. This policy aims to promote smooth coordination between medical insurance services and LTCI providers. Accordingly, the medical insurance system allows hospitals to receive additional fees by providing patient information to rehabilitation service providers in the LTCI system. A comprehensive database on acute, convalescent, and chronic phase stroke patients and seamless cooperation between the medical care system and LTCI system is expected to be established in the future. There are only 2,456 board-certified physiatrists in Japan, and many medical schools lack a department for rehabilitation medicine; establishing such a department at each school is encouraged to teach students efficient medical care procedures, to conduct research, and to facilitate the training of personnel in comprehensive stroke rehabilitation.